Novel copy number variations within SYCE1 caused meiotic arrest and non-obstructive azoospermia - Yuhua Huang; Ruhui Tian; Junwei Xu; Zhiyong Ji; Yuxiang Zhang; Liangyu Zhao; Chao Yang; Peng Li; Erlei Zhi; Haowei Bai; Sha Han; Jiaqiang Luo; et al. (BMC, 2022)
Abstract Background Non-obstructive azoospermia (NOA) is the most severe disease in male infertility, but the genetic causes for majority of NOA remain unknown. Methods Two Chinese NOA-affected patients were recruited to identify the genetic causal factor of infertility. Whole-exome sequencing (WES) was conducted in the two patients with NOA. Sanger sequencing and CNV array were used to ascertain the WES results. Hematoxylin and eosin (H&E) staining and immunofluorescence (IF) were carried out to evaluate the stage of spermatogenesis arrested in the affected cases. Results Novel heterozygous deletion (LOH) within SYCE1 (seq[GRCh37] del(10)(10q26.3)chr10:g.135111754_135427143del) and heterozygous loss of function (LoF) variant in SYCE1 (NM_001143763: c.689_690 del:p.F230fs) were identified in one NOA-affected patient. While homozygous deletion within SYCE1 (seq[GRCh37] del(10)(10q26.3)chr10:g.135340247_135379115del) was detected in the other patient with meiotic arrest. H&E and IF staining demonstrated that the spermatogenesis was arrested at pachytene stage in the two patients with NOA, suggesting these two novel CNVs within SYCE1 could lead to meiotic defect and NOA. Conclusions We identified that two novel CNVs within SYCE1 are associated with meiotic arrest and male infertility. Thus, our study expands the knowledge of variants in SYCE1 and provides a new insight to understand the genetic etiologies of NOA.